Freire’s view of a progressive and humanistic education: Implications for medical education - Dario Torre; Victoria Groce; Richard Gunderman; John Kanter; Steven Durning; Steven Kanter (MedEdPublish, 2017)
Brazilian educator Paulo Freire argues that the purpose of education is to liberate human potential and, thus, is much more than a teacher simply depositing information into the mind of a learner. His ideas are important to medical education because 1) they strengthen the philosophical underpinning of practices in medical education (for example, Freire's dialogical approach to learning vis-à-vis the banking model of education adds philosophic strength to the use of problem-based learning as a primary learning modality); 2) they encourage medical educators to confront directly the tension between teaching for conformity, which many would argue is key to performing a good and reliable physical examination, and teaching to liberate human potential, which is critical to preparing physicians to question current assumptions, practices, and knowledge; and 3) they encourage expanded thought about approaches to medical education, for example in the choice of pedagogical method, defining the role of the educator, and the use of experiences like service learning.